Pengaruh Gaya Kepemimpinan, Motivasi, Budaya Organisasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan (Studi Kasus Pada PD. BKK Se-Kabupaten Wonogiri) - PRIHANDAYANI, HETTY, Drs. EkoSugiyanto, M. si (2017)
This research aims to determine the effect of leadership style, motivation, organizational culture, and work environment on employee performance of all over PD. BKK in Wonogiri. In this study the type of data used is primary data or questionnaire with technique sampel collection techniques used are questionnaires and interviews, research conducted with sensus sampling. The sampel in this study amounted to 142 in PD. BKK Wonogiri returned to the author amounted to 93 sampels. Based on the analysis it can be concluded that the leadership style not significant effect on the employee performance, the motivation significant effect on the employee performance, the organizationa culture not significant effect on the employee performance, the work environment not significant effect on the employee performance